MAKNA ILUSTRASI SAMPUL MAJALAH TEMPO EDISI ‘KEJARLAH DAKU, KAU KUBEKAP’ - Ahdiyat, Azhar Natsir; Saidi, Acep Iwan; Sachari, Agus (Wimba : Jurnal Komunikasi Visual, 2024)
Cases of corruption involving well-known figures in Indonesia always draw public attention. One such figure is the politician Setya Novanto, who was embroiled in the e-KTP corruption case in 2017. This case was considered a significant corruption case, thus the topic also expanded and became a concern for the society. Due to the importance of this case, Setya eventually became the main figure in the cover illustration of Tempo Magazine's edition titled "Kejarlah Daku, Kau Kubekap" (Chase Me, I'll Smother You) which indicates certain implicit elements including signs and meanings that are interesting to uncover. The purpose of this study is to analyze the visual sign structure and reveal the meanings contained in the cover illustration of Tempo Magazine's edition "Kejarlah Daku, Kau Kubekap". Unveiling the meanings behind the signs present in the magazine cover illustration is made possible using a visual semiotics approach, specifically Barthes' semiotics concept. This study concludes that the meaning contained in the cover illustration of Tempo Magazine is Tempo highlighting news about indications of Setya Novanto's dramatic steps using the central government as a hiding tool from the pursuit of the Corruption Eradication Commission (KPK) related to the e-KTP corruption case. keywords: illustration, magazine cover, visual semiotics, signs, meanings.